Semi-automatic model to colony forming units counting - Diana Carolina Meneses-Cabezas; Yuliana Zapata-Serna; Yeison Alberto Garces-Gomez; Jesus Emilio Pinto-Lopera (Institute of Advanced Engineering and Science, 2023)
Colony forming units counting is a conventional process carry out in bacteriological laboratories, and it is used to follow the behavior of bacteria in different conditions. Currently exist different systems, automatic or semi-automatic, to counting colony forming units exits, but, in general, many laboratories continue using manual counting, which consumes considerable time and effort from researchers and laboratory employees. This paper presents a mathematical model carry out to segment the colony forming units and, in this way, counting them from a digital image of the sample. The method uses the color space information of some points in the image and shows good behavior for images with many or few colony forming units in the sample, according to manual counting. The results show efficiencies close to 98% with MacConkey agar.